Utilization of kepok banana peel waste as liquid organic fertilizer for the growth and yield of sweet corn (Zea mays saccharata Sturt L.) plants - Kalista Setia Anatolana; Ariefin, Muhammad Noor; Devi Liana (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
This study aims to determine the response and appropriate concentration of liquid organic fertilizer from banana peel waste on the growth and yield of sweet corn (Zea mays saccharata Sturt L.). The research method was a field experiment using a Randomized Block Design with various concentrations of liquid organic fertilizer from Kepok banana peel waste. The treatments are P0 = 0 ml/litre of water, P1 = 50 ml/litre of water, P2 = 100 ml/litre of water, P3 = 150 ml/litre of water, P4 = 200 ml/litre of water, and P5 = 250 ml/litre of water. Each treatment was repeated four times. The data obtained in this study were analyzed using Analysis of Variance at the 5% error level and followed by the Duncan Multiple Range Test (DMRT).  The results showed that the application of various concentrations of organic liquid fertilizer made from Kepok banana peel has a significant effect (p<0.05) on plant height, leaf count, stem diameter, cob length without husk, cob diameter without husk, and cob weight without husk. It can be concluded that the treatment with the concentration of Kepok banana peel organic liquid fertilizer at P2 (100 ml/litre of water) yielded the best results for plant height, leaf count, stem diameter, cob length without husk, cob diameter without husk, and cob weight without husk.